2022
DOI: 10.3390/su14159033
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice towards the Use of Over-the-Counter Medicines: An Online Survey among Bruneian Adults amid the COVID-19 Pandemic

Abstract: Globally, self-medication has increased, where 25% of adults use OTC medicines. This research is intended to assess the knowledge, attitude and practice regarding OTC medicines among adults in Brunei Darussalam. An online cross-sectional survey was performed using a questionnaire adapted from similar research conducted among students in Brunei Darussalam. A total of 364 responses were collected, where the median age of the study participants was 23 years. The mean knowledge score was 7.3 out of 9, with most re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…As for education, there was a clear trend towards more OTC medication use among parents with an undergraduate education. Similarly, two clinical studies showed that almost all of the students (99.7% and 92.3%), including undergraduates and postgraduates, had a positive attitude towards the use of OTC medications, and only a few students used OTC medicine inappropriately, such as not reading the instructions or taking more than the recommended dose [18,19]. We also found an explicit association between education and self-medication with OTCs (p < 0.001).…”
Section: Discussionsupporting
confidence: 67%
“…As for education, there was a clear trend towards more OTC medication use among parents with an undergraduate education. Similarly, two clinical studies showed that almost all of the students (99.7% and 92.3%), including undergraduates and postgraduates, had a positive attitude towards the use of OTC medications, and only a few students used OTC medicine inappropriately, such as not reading the instructions or taking more than the recommended dose [18,19]. We also found an explicit association between education and self-medication with OTCs (p < 0.001).…”
Section: Discussionsupporting
confidence: 67%